The Civil War years : a day-by-day chronicle of the life of a nation - Denney, Robert E. (New York : Sterling Signature, 2011)
This book allows the reader to experience the Civil War as the struggle unfolded. Denney augments his daily entries with generous doses of eyewitness testimony. Here are the words of the soldiers, sailors, and civilians of the North and South, woven together in a narrative.--[from Foreword].
1861 -- 1862 -- 1863 -- 1864 -- 1865.
"The text featured in this edition is abridged from [the edition] originally published ... in 1992"--Page [iv].
Includes index.
Keywords: United States -- History -- Civil War, 1861-1865 -- Chronology; United States -- History -- Civil War, 1861-1865 -- Sources; United States; United States -- History -- 1861-1865, Civil War -- Chronology; United States -- History -- 1861-1865, Civil War -- Sources; 1861-1865; Chronologies; History; Sources